Strategy and generation of value in Colombian service-providing companies - Ramiro Parra Hernández; Beatriz Elena Guzmán Díaz; Edwin Tarapuez Chamorro (Cuadernos de Administración, 2018)
This research aims to identify the relationship between strategy and value generation in service-providing companies that have won the Premio Colombiano a la Calidad (Colombian Management Quality Award) from the Ministerio de Comercio, Industria y Turismo (Ministry of Commerce, Industry and Tourism) in the period 2013-2014, an accolade created to stimulate companies that stand out for having a practical approach towards aspects such as the creation of value for stakeholders. The methodology is of deductive, exploratory and descriptive nature, while information was obtained from seven companies through multiple case analysis. The results indicate that the studied companies display a direct relationship between strategy and value generation, have an integral, holistic and systemic vision, have a formal strategic process of formulation, implementation and control, bestow some participation onto their stakeholders, and acknowledge human talent, corporate image and financial resources as strategic factors. We concluded that the strategic orientation of companies for the generation of value is focused on the type of product or service, size and growth, profitability and market category. Moreover, the analyzed companies reckon fundamental elements in their value-creating system to generate a competitive advantage.